If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 8y = -9 Solving 15x + 8y = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. 15x + 8y + -8y = -9 + -8y Combine like terms: 8y + -8y = 0 15x + 0 = -9 + -8y 15x = -9 + -8y Divide each side by '15'. x = -0.6 + -0.5333333333y Simplifying x = -0.6 + -0.5333333333y
| 21+27m=28+20m | | 4y^2+7=263 | | 170=-8(8p+3)+2 | | 3.8q-4.5-5.9q=-1.1q-4.5 | | 8x-3x+93=8x+51 | | 5x-23=3x-15 | | (1200-60x)(20+2x)= | | y=18x+5 | | -2-10n=68 | | 4(7-6x)=-20 | | 21+23=35+16 | | Log[4](33.3)= | | w+6= | | -4(-2+a)=52 | | x/(x-3)=8 | | 12x/(-4x) | | -5(m-5)=-60 | | a+-3+3=-2 | | 2.9(-5-1)-4.4(-5-7)= | | 175m-75m+58500=60300-200m | | x(3+3)=64.5 | | 7(2h-4)+3h=108 | | x(2+2)=64.5 | | 2.5x+0.5x=5+3.5x | | 360-(13x)=114 | | x(2+2)=43 | | x+2+2=43 | | 3/4×36 | | (8+3x+5x^2+8x^3)+(5-3x+5x^2-8x^3)= | | 12x-34=85-5x | | 4x=2y-4-20 | | 7(5x-2)=6(6x-1)x |